Meta-analysis on the relation between visuomotor integration and academic achievement: Role of educational stage and disability. (February 2022) - Khatib, Lora; Li, Yaoran; Geary, David; Popov, Vitaliy
Abstract: Visuomotor integration (VMI) is the ability to coordinate visual perception and motor functioning. Measures of VMI are commonly used to assess children's readiness for academic learning. Attention and investments towards VMI development are mainly focused on early learners, but some empirical research indicates sustained relations between VMI and academic achievement through middle and high school. To determine the relations between VMI and academic achievement, as well as moderating factors, we conducted a multilevel meta-analysis using a total of 96 articles and 266 effect sizes published over the past 60 years. The pooled effect size revealed moderate correlations between VMI and mathematical ( r  = 0.39) and reading ( r  = 0.34) achievement. Educational stage, disability, and intelligence were significant moderators of the relation between VMI and mathematics achievement, whereas educational stage and subdomains of reading skills were significant moderators of the relation between VMI and reading achievement. Implications and future research directions are discussed. Highlights: This study synthesized findings from 102 articles and 272 effect sizes published over the past 60 years through multilevel meta-analyses. The pooled effect size revealed moderate correlations between VMI and mathematical ( r = .38) and reading ( r = .34) achievement. Educational stage was a significant moderator of the relations between VMI and mathematical and reading achievement but the decreases in the magnitude of the relation between VMI and achievement across educational stages were more significant and notable for reading than for mathematics. Disability and intelligence were significant moderators of the relation between VMI and mathematics achievement. Subdomains of reading skills (e.g., letter-word identification) instead of disability or intelligence were significant moderators of the relation between VMI and readingachievement.